Investigation of the rearrangement in alkyl-bridged bis(carbamoyldiaziridine) derivatives - Kamuf, Matthias; Rominger, Frank; Trapp, Oliver (European journal of organic chemistry, 2012)
The thermal treatment of alkyl-bridged bis(carbamoyldiaziridine) derivatives in toluene at 100 °C led to the formation of new saturated five- and six-membered 1,3-diaza-heterocyclic compounds from ethylene- or propylene-bridged bis(carbamoyldiaziridine) derviatives, respectively. Detailed experimental investigations of this reaction revealed an unprecedented intramolecular eliminative rearrangement, involving the two adjacent diaziridine moieties. The loss of a three-carbon fragment by elimination of acetone during the reaction was confirmed by GC-MS measurements. The products of the rearrangement were fully characterized, and their structures were confirmed by X-ray crystal structure analysis. Furthermore, a reaction mechanism of the eliminative rearrangement was proposed, and the reaction pathway was corroborated by DFT calculations of gas-phase model structures at the B3LYP/6-31G** level.